FİNANCİNG SMALL AND MEDİUM ENTERPRİSES (SMES) BY INİTİAL PUBLİC OFFERİNG (IPO): ISE GROWİNG COMPANİES MARKET (GCM) (Third Sector Social Economic Review, 2013)
Small and medium enterprises (SMEs) are very important with regard to their share in both the number of all the enterprises and, employment and value added. However, they may face some finacial problems. It can be claimed that Long-term financial problem is at the begining of these problems. It is considered that available financial methods for SMEs are unsatisfactory. For all that, an securities exchange for SMEs can be contribute to solving long-term financial problem. Thus, ISE Growing Companies Market (GCM) established in 2011 is an securites exchange for SMEs in Turkey, which is formed for this porpose. In this study, the application for SMEs securities exchange in Turkey is examined together the ones in the World and evaluated in point of its various aspects.
Keywords: long-term financial problem; SMEs stock exchange; ISE GCM